Local-level implementation of Social Emotional Learning in arts education: moving the heart through the arts. Issue 3 (3rd July 2021) - Eddy, Martha; Blatt-Gross, Carolina; Edgar, Scott N.; Gohr, Adam; Halverson, Erica; Humphreys, Kathryn; Smolin, Louanne
Abstract: This group of portraits paints a picture of how educational policies across different regions of the United States afford varying experiences using arts disciplines pedagogically for SEL instruction. Each policy-supported portrait interfaces with SEL to teach competencies and report enhancement in personal emotional growth, social awareness, critical thinking, problem-solving, information management, global innovation, and artistic competency. Through reading these portraits, rationales emerge for the need to enhance interpersonal collaboration, verbal, non-verbal and esthetic communication, collaborative creativity, and cultural awareness in teacher education, in curricular design, and school-policy.